Analysis of the Application of Accounting in Barbershop Businesses in Purwokerto City, Banyumas Regency - Eraerawati, Ria; Hadi, Syamsul (International Journal of Integrative Sciences, 2025)
This research aims to analyze the implementation of accounting in barbershop businesses in Purwokerto City, Banyumas Regency. The method used in this study is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results of the study indicate that most barbershop businesses in Purwokerto have not yet optimally implemented accounting practices. Financial recording is still done in a simple manner and does not comply with applicable accounting standards. This is due to a lack of understanding among business owners regarding the importance of implementing accounting and the limitations of available resources. Based on these findings, it is necessary to provide education and assistance to barbershop business owners so they can properly implement accounting practices. Proper accounting implementation will help in financial control, performance measurement, and serve as a basis for accurate business decision-making. Ultimately, this can support the growth and sustainability of barbershop businesses in Purwokerto